Análise de desempenho de um motor diesel turboalimentado ottolizado para gás natural - Ferraz, Fagner Barbosa (2014)
A large number of national companies has been using diesel gensets as an alternative to the electricity supplied by the local utility. Therefore, generators are used as an emergency power system or during peak hours. Peak hour in Brazil is between 5 to 10 p. m. As we know diesel engines contribute to the large increase in environmental pollution, since the diesel exhaust may contain fine particles associated with negative health effect, toxic air contaminants, as NOx and SOx. On the other hand, Natural gas is considered as a suitable choice rather than the use of diesel, because it possesses high calorific power, clean burning, and proper octane level for Otto cycle engine. The present work deals with the performance analysis of a Perkins engine turbocharged, diesel, model 1104C-44TA, converted into an Otto cycle engine to run on natural gas, also identifying the limiting factors of power in these types of engines. Giving the importance of the compression rate on the Diesel to Otto cycle conversion, the evaluation of the Perkins processed engine happened under the influence of three different rates: 7.6:1; 8.7:1 and 12.3:1. For each compressed rate, and stoichiometric mixture, the task was to choose the spark advance to guarantee best performances to the engine. All tests were performed with a hydraulic dynamometer. The results showed that, the best combination of those parameters are not sufficient to ensure the highest performance of a diesel converted engine. There was a consubstantial rise in temperature of the exhaust gases and on the turbine walls, due to the increase in the exhaust gases volume, compared to that of the burnt gases withdrawn from the original engine, impairing the efficiency and lifespan of the engine components. It was found, by energetic analysis, the compression ratio of 8.7:1, was the most efficient, among the other two, assuring the engine its best performance. As expected, at the compression rate of 7.6:1 the exhaust gases presented the highest temperatures. At compression ratio of 12.3:1 the gas emissions of the converted engine delivered highest NOx level and the lowest level of unburned hydrocarbons at the exhaust. Keywords: Diesel Turbocharged Engine. Diesel to Otto Cycle Conversion Process. Natural Gas. Performance. Energy Balance